2020
DOI: 10.1111/pai.13366
|View full text |Cite
|
Sign up to set email alerts
|

Detection of the SARS‐CoV‐2 in different biologic specimens from positive patients with COVID‐19, in Northern Italy

Abstract: , the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) started a new pandemic respiratory disease named 2019 novel coronavirus infectious disease (COVID-19). 1,2 Lombardy Region (northern Italy) has been involved in a dramatic COVID-19 epidemic episode since February 20 with a rapid increase in the rate of infected patients. At the time of writing, the number of infected people in Italy was higher than 97,000 with more than 40% of cases reported in the Lombardy Region. 2 To date, the diagnosis of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…The accumulation of the first cases in those who came into contact with the Wuhan South China Seafood City Market in the south of Wuhan suggested that the causative agent was a zoonotic coronavirus [6]. However, soon the reporting of imported cases and the increase in the epidemic rate [7] were shown as evidence of human-to-human transmission [8], and it was understood that this transmission occurred [6][7][8][9][10] by droplet route, contact with the surfaces of the secretions of infected individuals, and possible faecal-oral transmission [9,10]. Given this information, being able to diagnose sick individuals early plays a crucial role in bringing the disease under control by breaking the chain of contact [11].…”
Section: Introductionmentioning
confidence: 99%
“…The accumulation of the first cases in those who came into contact with the Wuhan South China Seafood City Market in the south of Wuhan suggested that the causative agent was a zoonotic coronavirus [6]. However, soon the reporting of imported cases and the increase in the epidemic rate [7] were shown as evidence of human-to-human transmission [8], and it was understood that this transmission occurred [6][7][8][9][10] by droplet route, contact with the surfaces of the secretions of infected individuals, and possible faecal-oral transmission [9,10]. Given this information, being able to diagnose sick individuals early plays a crucial role in bringing the disease under control by breaking the chain of contact [11].…”
Section: Introductionmentioning
confidence: 99%